1990
DOI: 10.1002/ajhb.1310020505
|View full text |Cite
|
Sign up to set email alerts
|

Determining growth faltering with a tracking score

Abstract: A tracking score for determining growth faltering in children was developed and tested. A graphical method was developed for classifying by visual inspection whether or not a given child had faltered in growth. This method was used to classify all children in a sample of Guatemalan children as to faltering in both weight and length between 9 and 24 months of age; 80 of 345 children had faltered in weight, and 44 of 336 children had faltered in length. The accuracies for determining this faltering of seven vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…16 In general, the large-scale use of a definitive measurement approach is prohibitive due to logistical challenges and the time it takes to obtain each measurement, so the development of reference or field measures is critical to being able to measure a phenomenon efficiently. Our analytical approach of developing and using a definitive classification to establish accuracy has been used successfully for validating measures of growth faltering 17 and household or adult food security. 18−20 In this study, in-depth interviews with children were used as the basis for definitive classification of children as experiencing or not experiencing each of 6 subdomains that comprise child food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…16 In general, the large-scale use of a definitive measurement approach is prohibitive due to logistical challenges and the time it takes to obtain each measurement, so the development of reference or field measures is critical to being able to measure a phenomenon efficiently. Our analytical approach of developing and using a definitive classification to establish accuracy has been used successfully for validating measures of growth faltering 17 and household or adult food security. 18−20 In this study, in-depth interviews with children were used as the basis for definitive classification of children as experiencing or not experiencing each of 6 subdomains that comprise child food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…For indicators such as whether or not a young child has faltered in growth 36 or whether or not a child has experienced food insecurity, 37 T i is binary. For example, children with growth faltering have T i positive and children without growth faltering have T i negative.…”
Section: Establishing Validity and Cross-context Equivalencementioning
confidence: 99%
“…The analysis demonstrated that this measure had superior and excellent accuracy, with areas under the curve > 0.9 for both weight and length. 36 For some subfields, establishing the validity of measures is hampered by a lack of a definitive measure to use as a criterion to compare reference or field measures. Assessment of usual dietary intake, for example, presents many challenges to establishing validity.…”
Section: Establishing Validity and Cross-context Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, longitudinal modeling of linear growth can be used, as has been done to demonstrate evidence of catch-up growth at some ages after bouts of Cryptosporidium parvum infection (50) and diarrhea (51,52). Another possible method that theoretically could be adapted was developed for identifying children in rural Guatemala who faltered in growth during the age of 9-24 mo by comparing growth during this period with that of the previous period (53). This method capitalized on the alignment of the period of growth inhibition for most children as starting at ∼9 mo when children were consuming substantial foods other than human milk and were more exposed to pathogens in their physical environment.…”
Section: Catch-up Growthmentioning
confidence: 99%